2015
DOI: 10.1007/s00011-015-0850-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin-6 gene polymorphism with coronary artery disease: an updated systematic review and cumulative meta-analysis

Abstract: The C allele of -174G/C polymorphism may associate with increased sensibility to CAD among Caucasians in overall analysis. Nevertheless, the effect is interfered by heterogeneity across the included studies. The C allele of -572G/C polymorphism may decrease the risk of CAD in Chinese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 49 publications
3
35
0
3
Order By: Relevance
“…The risk allele for IL6 rs1800795 our study was C. This is in agreement with another study carried out in high-risk Pakistani families where the minor allele C showed high prevalence in cases compared with controls 10. While a strong association of the risk allele C was demonstrated with CAD in the Chinese18 and Indians23 no such association was seen in the Tunisians 24. The Northwick Park Heart study on the other hand showed that the IL6 rs1800795 GC (heterozygotes) were significantly at a greater risk to develop CAD as compared with the CC homozygotes 25.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The risk allele for IL6 rs1800795 our study was C. This is in agreement with another study carried out in high-risk Pakistani families where the minor allele C showed high prevalence in cases compared with controls 10. While a strong association of the risk allele C was demonstrated with CAD in the Chinese18 and Indians23 no such association was seen in the Tunisians 24. The Northwick Park Heart study on the other hand showed that the IL6 rs1800795 GC (heterozygotes) were significantly at a greater risk to develop CAD as compared with the CC homozygotes 25.…”
Section: Discussionsupporting
confidence: 92%
“…Addressing this will require the discovery of additional loci to identify the molecular pathways underlying the pathogenesis of CAD. The cytokine gene promoter SNPs in our study were selected after a thorough literature search and from extensive meta-analyses18 47 which is considered to be the gold standard for SNP selection 12. Recent genome wide association studies and meta-analyses have identified cytokine genes and their variants (IL-18, IL-10, IL-6 and TNFA) as the potential CAD risk loci some of which significantly affect the serum cytokine levels 44 48 49.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the scope of our review did not account for the possible contribution of genetic variations leading to genetic predisposition of different ethnic groups and different HCV genotypes to CVD outcomes. In particular polymorphisms in cytokine genes or promoter regions may affect expression of inflammatory mediators and hence may affect CVD risk . Studies investigating genetic associations with inflammatory markers have been inconclusive and were not considered in the scope of this review.…”
Section: Discussionmentioning
confidence: 99%
“…Carriers of the−174G > C mutation have an increased risk of developing various major diseases, including Alzheimer disease 30 , CVD 31 , non-insulin-dependent diabetes mellitus 32 , bone fragility 33 , and systemic-onset juvenile chronic arthritis 34 . A genome-wide association study comparing >2,000 Chinese centenarians to middle-aged controls found that the SNP rs2069837 in IL6 was significantly associated with extreme longevity, confirming the role of IL-6 in conditioning morbidity and mortality, especially in old age 35 .…”
Section: Risk Factors and Causes Of Inflammageingmentioning
confidence: 99%